2018
DOI: 10.1175/jas-d-17-0353.1
|View full text |Cite
|
Sign up to set email alerts
|

Multilevel Tower Observations of Vertical Eddy Diffusivity and Mixing Length in the Tropical Cyclone Boundary Layer during Landfalls

Abstract: This study analyzes the fast-response (20 Hz) wind data collected by a multilevel tower during the landfalls of Tropical Storm Lionrock (1006), Typhoon Fanapi (1011), and Typhoon Megi (1015) in 2010. Turbulent momentum fluxes are calculated using the standard eddy-correlation method. Vertical eddy diffusivity Km and mixing length are estimated using the directly measured momentum fluxes and mean-wind profiles. It is found that the momentum flux increases with wind speed at all four levels. The eddy diffusivity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
12
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 34 publications
8
12
1
Order By: Relevance
“…The spatial patterns and magnitude of the coastal variations in K m values with u n are similar to the aircraft observation results of Zhao et al [22]. The slope of increasing K m with u n at <30 m s −1 is similar to the results of Zhang and Drenman [5], Tang et al [24], and Zhao et al [25]. The decreasing K m at wind speeds of >30 m s −1 is different from the observational results of hurricane eyewalls at 500 m altitude from Zhang et al [19], which shows that K m consistently increases with increasing u n to >40 m s −1 .…”
Section: Vertical Diffusion Transport Of Momentumsupporting
confidence: 88%
See 2 more Smart Citations
“…The spatial patterns and magnitude of the coastal variations in K m values with u n are similar to the aircraft observation results of Zhao et al [22]. The slope of increasing K m with u n at <30 m s −1 is similar to the results of Zhang and Drenman [5], Tang et al [24], and Zhao et al [25]. The decreasing K m at wind speeds of >30 m s −1 is different from the observational results of hurricane eyewalls at 500 m altitude from Zhang et al [19], which shows that K m consistently increases with increasing u n to >40 m s −1 .…”
Section: Vertical Diffusion Transport Of Momentumsupporting
confidence: 88%
“…Katz and Zhu [23] used observational data to evaluate surface layer flux parameterizations. Based on flux tower observations, Tang et al [24] concluded that K m values in a hurricane PBL are greater when the wind is blowing from inland than the ocean at u n of up to ~30 m s −1 during typhoon landfall. Zhao et al [25] analyzed mean wind profiles by a 350-m height flux tower during a typhoon landfall with u n up to ~33 m s -1 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Using the methodology discussed in Tang et al. (2018) it was found that the maximum value of l 2 did not exceed 100 m, whereas the original default was 300 m in the J. Han and Bretherton (2019) formulation.…”
Section: Introductionmentioning
confidence: 99%
“…Based on fast‐response wind data collected during typhoons in 2010, Tang et al. (2018) concluded that the VED in a hurricane PBL is greater for wind blowing from land than from the ocean. F. Zhang and Pu (2017) and F. Zhang et al.…”
Section: Introductionmentioning
confidence: 99%